Biostimulant Potential of Humic Acids Extracted From an Amendment Obtained via Combination of Olive Mill Wastewaters (OMW) and a Pre-treated Organic Material Derived From Municipal Solid Waste (MSW) - Palumbo, Giuseppe; Schiavon, Michela; Nardi, Serenella; Ertani, Andrea; Celano, Giuseppe; Colombo, Claudio M. (Frontiers in Plant Science, 2018)
Olive mill wastewaters (OMW) detain contain significant levels of phenolic compounds with antimicrobial/phytotoxic activity and high amounts of undecomposed organic matter that may a high pollutant load that exerts negative effects on soil biology because of significant levels in phenolic compounds with antimicrobial/phytotoxic activity and limited biodegradability, and high amounts of undecomposed organic matter. Among OMW detoxification techniques, those focusing on oxidative degradation of phenolic compounds are relevant those focusing on oxidative degradation of phenolic compounds to reduce their toxicity. The composting (bio-oxidation) process in particular, exploits exothermic oxidation reactions of by microorganisms to transform the organic matrix of OMW into an amendment biologically stable and feasible to use in agriculture. This process consists of an active phase, during which decomposition of organic compounds is rapidare rapidly decomposed, and a curing phase characterized by a slower decompositionbreakdown rate of the remaining materials, with the formation of humic substances (HS) as by-products. In this study, bio-oxidation of OMW was performed using a pre-treated organic material derived from municipal solid waste (MSW). The obtained amendment (OMWF) was stable and in accordance with the legislative parameters of mixed organic amendments. HS were then extracted from OMWF and MSW (control amendment, Amd-C, control), and, differences in structural and the properties of their humic acid (HA) fraction were investigated highlighted via spectroscopy (Fourier Transform Infrared FT-IR and RAMAN) spectroscopies, and Dynamic Light Scattering (DLS). To assay a potential use of HA as biostimulants fro for crops, 12-day old Zea Mays L. plants were supplied with individual HA at 0.5 mg and 1 mg C L-1 for two days. In general, HA from both amendments increased plant growth, with but HA from OMWF was being more effective at both dosages (plus 35-37%). Also, HA from OMWF enhanced both nitrogen assimilation and glycolysis by increasing the activity of nitrate reductase (~1.8-1.9 folds)(NR), phosphoglucose isomerase (PGI) (~1.8-2 folds) and pyruvate kinase (PK) (~1.5-1.8 folds), while HA from Amd-C targeted glycolysis preferentially. HA from OMWF however, significantly stimulated plant nutrition only only at lower dosage, perhaps because certain undetermined compounds in from detoxified OMW and incorporated in HA altered